A structured framework improves clinical patient assessment and nontechnical skills of early career emergency nurses: a pre–post study using full immersion simulation. Issue 15 (2nd May 2016) - Munroe, Belinda; Curtis, Kate; Murphy, Margaret; Strachan, Luke; Considine, Julie; Hardy, Jennifer; Wilson, Mark; Ruperto, Kate; Fethney, Judith; Buckley, Thomas
Abstract : Aims and objectives: The aim of this study was to evaluate the effect of the new evidence‐informed nursing assessment framework HIRAID (History, Identify Red flags, Assessment, Interventions, Diagnostics, reassessment and communication) on the quality of patient assessment and fundamental nontechnical skills including communication, decision making, task management and situational awareness. Background: Assessment is a core component of nursing practice and underpins clinical decisions and the safe delivery of patient care. Yet there is no universal or validated system used to teach emergency nurses how to comprehensively assess and care for patients. Design: A pre–post design was used. Methods: The performance of thirty eight emergency nurses from five Australian hospitals was evaluated before and after undertaking education in the application of the HIRAID assessment framework. Video recordings of participant performance in immersive simulations of common presentations to the emergency department were evaluated, as well as participant documentation during the simulations. Paired parametric and nonparametric tests were used to compare changes from pre to postintervention. Results: From pre to postintervention, participant performance increases were observed in the percentage of patient history elements collected, critical indicators of urgency collected and reported to medical officers, and patient reassessments performed. Participants also demonstrated improvement in each of the four nontechnical skills categories: communication, decision making, task management and situational awareness. Conclusion: The HIRAID assessment framework improves clinical patient assessments performed by emergency nurses and has the potential to enhance patient care. Relevance to clinical practice: HIRAID should be considered for integration into clinical practice to provide nurses with a systematic approach to patient assessment and potentially improve the delivery of safe patient care.